Pemberdayaan Masyarakat Melalui Pendampingan Pembuatan Kerupuk Kerang Darah untuk Meningkatkan Perekonomian Masyarakat di Desa Karya Indah, Kabupaten Pohuwato - Solang, Margaretha; Saman, Widya Rahmawaty; Husain, Ilyas; Kumaji, Syam; Retnowati, Yuliana; Santoso, Budy (Universitas Negeri Gorontalo, 2023)
KKN-MBKM is one of the media to carry out the tridharma functions of higher education for every lecturer. One of these tridharma is by carrying out community service. The problems obtained from Karya Indah Village which became the object included the absence of professional management and the absence of training and community development on how to process blood clams into crackers which can be used as a home-based business. The approach method in the program includes demonstrations and presentations on the process of processing blood clams into crackers and how to package blood clam crackers, all of these activities are accompanied by the implementing team. The results achieved in the KKN-MBKM program are blood clam cracker products that are packaged properly in plastic packaging as well as scientific articles. Direct practice is carried out to facilitate understanding for the target community. From the results of this practice, it is hoped that the community can apply the processing of blood clams into crackers which can improve the economy of the people of Karya Indah Village, Buntulia District, Pohuwato Regency, Gorontalo Province.